Global Development Finance 2006 : The Development Potential of Surging Capital Flows, Volume 2. Summary and Country Tables - World Bank (2012)
Global Development Finance is the World Bank's annual review of global financial conditions facing developing countries. The current volume provides analysis of key trends and prospects, including coverage of capital originating from developing countries themselves. Robust global growth and a favorable financing environment provided the context for a record expansion of private capital flows to developing countries in 2005. Many low-income countries still have little or no access to international private capital, and instead depend largely on official finance from bilateral and multilateral creditors to support their development objectives. Capital flows are changing due to financial integration among developing countries, financial innovations, domestic debt markets, and the global role of the Euro. Net official flows continue to decline as official lending falls and there is more aid and debt relief for the poorest countries. To ensure economic stability, developing countries must manage capital flows with effective macroeconomic policies, prudent accumulation of reserves, careful management of oil-export revenues, and improvements in standards for the corporate sector.